Characterization of CO and NO2 exposures of ice skating rink maintenance workers. Issue 2 (1st February 2019) - Cox, Aaron; Sleeth, Darrah; Handy, Rodney; Alaves, Victor
Abstract: Air quality is a common concern among indoor ice rink facilities due to the use of gasoline/propane ice resurfacing equipment. Although previous studies have investigated spectator, guest, and skater exposures, a review of the literature revealed little published research regarding ice maintenance employees' exposures. Ice maintenance includes edging and resurfacing. The resurfacer is commonly referred to as a Zamboni®. Edging is almost always followed by resurfacing, but resurfacing frequently happens independently of edging. The purpose of this study was to characterize ice rink maintenance employees' exposures to CO and NO2 . Employees from four ice rinks in Salt Lake County, Utah were sampled using direct reading instruments during routine ice maintenance activities. Maintenance was divided into four activities: 1) Edging only, 2) Resurfacing after edging (not including edging), 3) Edging and resurfacing (Activities 1 and 2 combined), and 4) Resurfacing only (independent of edging). Activities 1, 2 and 3 were sampled twenty-four (n = 24) times. Activity 4 was sampled eight times. Sampling results were graphed and summarized using descriptive statistics. The highest measured CO concentration was 202 ppm, which occurred during edging. Average CO concentrations for all activities ranged from 0 ppm to 60.4 ppm. Minimal CO exposure was observed when resurfacing occurred without edging, which implies that elevated CO exposure measured while using the resurfacer may be residual CO from prior edging activities. NO2 concentrations were negligible for all rinks and all activities. Results confirmed that gasoline edgers significantly contribute to indoor CO levels, with peak levels exceeding some recommended exposure levels. Indoor ice rink facilities should monitor employees' CO exposures and implement procedures to limit exposures. This may be achieved by limiting the number of laps taken with the edger or replacing gasoline powered edgers with electric edgers.